Advances in neuro-immune interactions in chronic pruritic dermatoses - Xinran LI; Yao CHEN; Fengxian LI (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2023)
Chronic pruritus is a clinical manifestation of a variety of cutaneous and systemic diseases. Persist chronic pruritus leads to a decreased quality of life. Nowadays the efficacy of traditional therapeutic regimens is not satisfactory, and the treatment of chronic pruritus is facing difficulties. Therefore, it is crucial to explore the pathogenesis of chronic pruritus and to develop new therapeutic strategies, including targeted drugs. This review focuses on the interaction between sensory terminals and immune cells in the skin and summarizes the progress on the mechanisms of chronic pruritic diseases such as atopic dermatitis, psoriasis, diabetic pruritus, and chronic pruritus of unknown origin. To elucidate the regulatory role of neuroimmune interaction in cutaneous inflammation and the pathological process of chronic pruritus can facilitate future basic and clinical research.